Notes on the name Lethrotrypes Jacobson, 1892 and taxonomic status of Parathorectes pueblai López-Colón et Bahillo De la Puebla, 2022 (Coleoptera: Geotrupidae) - I.V. Shokhin; M.Yu. Kalashian; T.L. Ghrejyan (Кавказский энтомологический бюллетень, 2024)
History of usage of the name Lethrotrypes Jacobson, 1892 is discussed. New synonyms are established: Lethrotrypes Jacobson, 1892 = Parathorectes López-Colón et Bahillo De la Puebla, 2022, syn. n., Trypocopris (Lethrotrypes) inermis (Ménétriés, 1832) = Parathorectes pueblai López-Colón et Bahillo De la Puebla, 2022, syn. n.